Lifetime smoking habits among Norwegian men and women born between 1890 and 1994: a cohort analysis using cross-sectional data. Issue 10 (17th October 2014) - Lund, Ingeborg; Lund, Karl Erik
Abstract : Objectives: Providing lifetime smoking prevalence data and gender-specific cigarette consumption data for use in epidemiological studies of tobacco-induced cancer in Norway. Characterising smoking patterns in birth cohorts is essential for evaluating the impact of tobacco control interventions and predicting smoking-related mortality. Setting: Norway. Participants: Previously analysed annual surveys of smoking habits from 1954 to 1992, and individual lifetime smoking histories collected in 1965 from a sample of people born in 1893–1927, were supplemented with new annual surveys of smoking habits from 1993 to 2013. Age range 15–74 years. Primary outcome measure: Current smoking proportions in 5-year gender-and-birth cohorts of people born between 1890 and 1994. Results: The proportion of smokers increased in male cohorts until the 1950s, when the highest proportion of male smokers (76–78%) was observed among those born in 1915–1934. Among women, the peak (52%) occurred 20 years later, in women born in 1940–1949. After 1970 smoking has declined in all cohorts of men and women. In the 1890–1894 cohorts, male smoking prevalence was several times higher than female, but the gap declined until no gender difference was present among those born after 1950. Gender-specific per capita consumption was even more skewed, and men have consumed over 70% of all cigarettes since 1930. The incidence of lung cancer for men peaked at around 2000, with the highest incidence rate estimated at ca. 38%. The incidence of lung cancer for women is still increasing, and estimated incidence rate for 2011 was 25.2%. Conclusions: In an epidemiological perspective, men have had a longer and more intense exposure to cigarettes than women. The gender-specific incidence of lung cancer reflects the gender difference in consumption over time.